PENGARUH F-COMMERCE BROWSING, F-COMMERCE USAGE INTENSITY TERHADAO F-COMMERCE IMPULSE PURCHASE PADA PENGGUNA FACEBOOK - Fadilla Riska Rahayu; Rina Suthia Hayu; Effed Darta Hadi (Faculty of Economics and Business Udayana University, 2022)
This study aims to examine the effect of f-commerce browsing and f-commerce usage intensity of f-commerce impulse purchase mediated by urge to purchase on users of the Facebook. The data was collected from 197 respondents who had made impulsive purchases using the Facebook. The data collection technique used a questionnaire that was distributed online through social media. The research measurement in this questionnaire consists of 16 questions to the respondent. Data analysis in this study used SEM-AMOS to see the relationship between variables. the research showed that; (1) f-commerce browsing has a positive effect on f-commerce impulse purchase; (2) f-commerce usage intensity has a positive effect on f-commerce impulse purchase; (3) f-commerce browsing has a positive effect on urge to purchase; (4) f-commerce usage intensity has a positive effect on f-commerce urge to purchase; (5) urge to purchase has a positive effect on f-commerce impulse purchase; (6) urge to purchase mediates the effect of f-commerce browsing on f-commerce impulse purchase; (7) urge to purchase mediates the f-commerce usage intensity on f-commerce impulse purchases.